Assessing Immunization Coverage and the Negative Impact of Local Vaccine Production Cessation in Ecuador - Esteban Ortiz-Prado; Lissette Carolina Villacreses-Brito; Jorge Vasconez-Gonzalez; Cristina Anabel Jacome; Marlon Arias-Intriago; Juan S. Izquierdo-Condoy (Vaccines)
Background: The COVID-19 pandemic highlighted vaccine importance while exposing inequities in global immunization, especially in LMICs like Ecuador. Local vaccine production ensures supply, reduces reliance on imports, and boosts health security. Understanding the relationship between local production and vaccination outcomes is crucial to addressing emerging public health challenges. Objective: The objective was to assess the impact of local vaccine production cessation on vaccination coverage rates for BCG- and DTP-containing vaccines. Methodology: This retrospective cross-sectional study analyzed vaccine coverage data from 2004 to 2023, focusing on key vaccines such as BCG and DTP, to assess the impact of the cessation of local vaccine production. Mann–Whitney U tests were conducted to compare vaccination coverage during the periods of local production (2004–2013) and post-production cessation (2014–2023). Historical context and policy implications were also evaluated to provide a comprehensive perspective. Results: A significant decline in vaccine coverage was observed following the cessation of local production. For BCG, median coverage decreased from 100% during the production period to 87.8% post-cessation (p < 0.0001). Similarly, DTP coverage dropped from a median of 99.5% to 83.4% (p < 0.0001). The findings highlight the critical role of local production in maintaining high vaccination rates and ensuring immunization equity. Conclusions: Reinvesting in local vaccine production is pivotal to improving immunization outcomes and strengthening Ecuador’s health security. International collaboration and strategic planning can help overcome current challenges, positioning Ecuador as a regional leader in vaccine production and public health resilience.